Arenas da vida: o discurso jurídico sobre a pessoa e a vida dos embriões in vitro - Santos, Filipe Lins dos (2018)
Law, as a field of knowledge production, does not become ready and finished in a norm or judgment of the court, but it is produced in the day to day of social and cultural relations. This is easily discernible when we bring to light the way in which the legal discourse has appropriated the categories of life and person to be able to judge the Direct Action of Unconstitutionality No. 3510, which dealt with the authorization of embryonic stem cell research. The importance of this judgment that occurred in 2008 was to perceive the set of strategies that were created within the discourse from cultural and social elements, to create and delimit social spaces for the application of the category of life and person, as well as other categories that were being put into question, such as abortion, death, DNA, soul and uterus. Therefore, the research problem rests on verifying the social and anthropological dynamics that went through the activation of these categories in the legal discourse and how this allows to see a set of interactions and conflicts that pass through values and serve as the basis for the strengthening of existing social relations or the emergence of new dynamics. In addition, an object that was the in vitro embryo that contained elements of nature and culture was at stake in this case, and assumed a hybrid character that led to the Federal Supreme Court (STF) to create the first public hearing of its history, in order to call the society and mainly researchers so that they could provide necessary elements in order to produce a decision that would put an end to the great question that permeated the judgment: Extraction of embryonic stem cells and the consequent death of the embryo Is In Vitro Abortion Practice? Would the embryo live in vitro? Is the embryo in vitro person? It is in this turbulent scenario that my research is situated. Thus, for the data collection I proceeded with a documentary ethnography based on the survey of all the documents that were part of the trial and extracting. The research brought as one of the results the way in which legal discourse appropriates certain values to deal with situations that are not limited to the scope of nature or culture, besides presenting a form of social gear that strengthens traditional values from a discursive logic of modernity and scientific advance.